Effect of Narcotic Analgesics on the Ultrastructure of the Eyeball (Experimental Study) - Pidvalna, Uliana; Kost, Andriy; Mateshuk-Vatseba, Lesya (Journal of Morphological Sciences, 2018)
Background The use of opioids among people of the young and working age has sharply increased in recent years simultaneously with the outbreak observed in the general population.Objective To determine the trigger mechanism of the destructive effect of narcotic analgesics on the ultrastructural level of the vascular tunic of the eyeball. Methods: This experimental study was performed on 26 male rats aged 3.0 months and body weight 160–180 g with daily intramuscular injection of Nalbuphine hydrochloride during 4 weeks. The material for the study was represented by ultramicroscopic sections of the vascular tunic of the eyeball.Results In comparison with the control group there was observed swelling of the cytoplasm and the nuclei of endotheliocytes, considerably narrowed lumens of the capillaries. Plasmolemma of endotheliocytes forms protrusions into the lumen of endotheliocytes forming microvilli. Changes of destructive nature took place in the elements of the smooth endoplasmic reticulum and mitochondrial complex. Signs that are characteristic of sclerosis were found in the surrounding connective tissue complex. In particular, lesions of endothelium and basement membrane of the elements of hemomicrocirculatory bloodstream, epithelium of the ciliary processes, cellular and non-cellular elements of the iris and the uvea proper have studied.Conclusion The databased on the experimental model allow extrapolation the results obtained to humans. It is confirmed that the development of angiopathy is the trigger mechanism of the destructive effect of narcotic analgesics.
Keywords: analgesics; opioids; capillaries; endothelium; animal experiment